Correlation between tobacco control policies, consumption of rolled tobacco and e-cigarettes, and intention to quit conventional tobacco, in Europe. Issue 2 (17th February 2016) - Lidón-Moyano, Cristina; Martín-Sánchez, Juan Carlos; Saliba, Patrick; Graffelman, Jan; Martínez-Sánchez, Jose M
Abstract : Objective: To analyse the correlation between the implementation of tobacco control policies and tobacco consumption, particularly rolling tobacco, electronic cigarettes (e-cigarettes) users and the intent to quit smoking in 27 countries of the European Union. Design: Ecological study with the country as the unit of analysis. Data sources: We used the data from tobacco control activities, measured by the Tobacco Control Scale (TCS), in 27 European countries, in 2010, and the prevalence of tobacco consumption data from the Eurobarometer of 2012. Analysis: Spearman correlation coefficients (rsp ) and their 95% CIs. Results: There was a negative correlation between TCS and prevalence of smoking (rsp =−0.41; 95% CI −0.67 to −0.07). We also found a negative correlation (rsp =−0.31) between TCS and the prevalence of ever e-cigarette users, but it was not statistically significant. Among former cigarette smokers, there was a positive and statistically significant correlation between TCS and the consumption of hand-rolled tobacco (rsp =0.46; 95% CI 0.06 to 0.70). We observed a similar correlation between TCS and other tobacco products (cigars and pipe) among former cigarette smokers. There was a significant positive correlation between TCS and intent to quit smoking in the past 12 months (rsp =0.66; 95% CI 0.36 to 0.87). Conclusions: The level of smoke-free legislation among European countries is correlated with a decrease in the prevalence of smoking of conventional cigarettes and an increase in the intent to quit smoking within the past 12 months. However, the consumption of other tobacco products, particularly hand-rolled tobacco, is positively correlated with TCS among former cigarette smokers. Therefore, tobacco control policies should also consider other tobacco products, such as rolling tobacco, cigars and pipes.